Role of pH on synthesis and characterization of cerium oxide (CeO2) nano particles by modified co-precipitation method. (March 2019) - Ramachandran, M.; Subadevi, R.; Sivakumar, M.
Abstract: A facile synthesis has been made to prepare cerium oxide (CeO2 ) nano particles via modified co-precipitation method using different pH values viz, 9 to 12 in steps of 1. The as prepared powders have been systematically studied to analyze their structure, morphology and photoluminescence properties. The representative samples have been analyzed through TEM and XPS analyses. The crystallite size has been decreased upon increasing the pH of the environment. When pH of the solute reached 12, the particle size is reached to 27 nm, which is ascertained through TEM analysis. Highlights: CeO2 nano particles have been prepared under various pH values via modified co-precipitation method. The crystallite size has been decreased upon increasing the pH. When pH = 12, the spherical morphology was obtained with the particle size of 27nm. This nano sized particle is expected to be a suitable filler candidate in polymer electrolytes for Lithium batteries.